Association of Serum Copper Levels and Amine Oxidase Copper Gene 1 (AOC1) with Migraineurs - Somavarapu Thomas, Anne Sahithi; Saraswathy, Radha; Anne, Anuhya; Thayanithy, Muthu (Applied Science and Engineering Progress, 2022)
Migraine is a common neurovascular multifactorial disease with biochemical abnormalities in the central nervous system (CNS). It is characterized by episodes of frequent headaches, affecting about 14% of the world’s population. Trace elements are essential to play an important role in neurotransmission and causing oxidative stress in patients with migraine. Also, it is hypothesized that Histamine (biogenic amine), catabolized by Diamine oxidase (DAO), induces a vascular headache. DAO contains Copper as a cofactor and is coded by the Amine oxidase copper containing 1 (AOC1) gene. This study aims to determine the level of serum copper (Cu), an association of the AOC1 gene and antioxidant capacity in migraine patients. In this study, a total number of 200 individuals (patients and controls) were equally distributed in each group according to demographic details obtained. The results obtained from this study were found to be significant to migraine. The frequency of T allele (rs10156191) in exon 4 AOC1 was 7.5% in migraineurs OR of 16.13; 95% CI- 0.63 to 47.97, and the p-value was observed to be 0.074. The mean concentration of Cu was found to be 0.09 ± 0.02 mg/L and 0.22 ± 0.10 mg/L in patients and controls, respectively. Antioxidant capacity of serum was found to be lower in patients (3 ± 1.2 μM ascorbic acid equivalents) when compared to controls (7 ± 0.9 μM ascorbic acid equivalents). Decreased Cu and a nonsynonymous of rs10156191 are associated with migraine, which may decrease DAO activity. Further research, needs to be focused on the DAO activity that can determine the migraine-inducing effect.